2016
DOI: 10.24953/turkjped.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Change of Helicobacter pylori prevalence in a decade among children undergoing endoscopy

Abstract: A total of 380 children, 131 in Group I and 249 in Goup II were recruited in the study. H. pylori postivity was found to be higher in Group I (% 48.1 and % 23.1, respectively, p < 0.001). Gastritis and atrophy were associated with H. pylori and both were more prevalent in Group I (p < 0.001). Our study demonstrates that H. pylori prevalence is decreasing in a pediatric population undergoing EGD in Ankara. This is the most recent study regarding pediatric H. pylori prevalence change in Turkey that we know of.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…In the last decades, several socioeconomic changes, such as improved living standards and eradication therapy strategies, occurred in several Western countries, including Portugal. In this setting, we would expect a gradual decrease in the prevalence of this infection in Portugal, similarly to that observed in other developed and developing countries 30,38,39 . Recent H. pylori infection prevalence studies in Portuguese children and adolescents are scarce.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In the last decades, several socioeconomic changes, such as improved living standards and eradication therapy strategies, occurred in several Western countries, including Portugal. In this setting, we would expect a gradual decrease in the prevalence of this infection in Portugal, similarly to that observed in other developed and developing countries 30,38,39 . Recent H. pylori infection prevalence studies in Portuguese children and adolescents are scarce.…”
Section: Discussionsupporting
confidence: 75%
“…this setting, we would expect a gradual decrease in the prevalence of this infection in Portugal, similarly to that observed in other developed and developing countries. 30,38,39 Recent H. pylori infection prevalence studies in Portuguese chil- Martel and Parsonnet et al reported no significant gender difference between the infected and non-infected children. 22,30,33,[41][42][43] Contrarily, Ferrari's retrospective study, which includes patients with ages ranging from 9 to 96 years old, found higher infection prevalence in males in all age groups, including the group younger than 20 years.…”
Section: Discussionmentioning
confidence: 97%
“…However, in Yaman et al's(8) study, a decrease in the prevalence of Hp in children in our country was reported in the last two decades. In our study, NSAID (15.2%) was the highest risk factor in the Hp infection-negative group.…”
mentioning
confidence: 54%
“…In our country, there are similar studies showing the trend of HP in the same region over a period of time. 12 However, our study is valuable in terms of showing the continuous trend in a single center over a long period of time. Therefore, our study will contribute to the literature.…”
Section: Discussionmentioning
confidence: 99%
“… 25 In a study conducted in Ankara, while the prevalence of HP was 48.1% in 2002-2003, it was found to be 23.1% in 2012-2013 in the same center and was statistically significant ( P < .001). 12 In a meta-analysis published in 2022 and including 198 articles, the global prevalence of HP in children was 32.3%. In the same meta-analysis, the association of HP positivity with low economic status, having more children, sharing the same room, having no sewage system, having an infected family member, and drinking untreated water was statistically significant.…”
Section: Discussionmentioning
confidence: 99%